Features of iNOS activity in the skin lesions of patients with psoriasis and concomitant hypertension - G.І. Makurina; M.М. Baudarbekova (Zaporozhye State Medical University, 2016)
Objective: To identify the features of the activity of nitric oxide synthase by immunohistochemical study of skin samples in patients with psoriasis and concomitant hypertension. Materials and methods. Specimens for immunohistochemical studies were taken from the surgical specimens of 40 psoriasis patients, including 20 with psoriasis and essenthial hypertension, 20 only with psoriasis, the control group consisted of 20 healthy individuals. For the diagnosis of the basic processes in the skin histopathological paraffin tissue sections were stained with hematoxylin and eosin. Immunohistochemical determination of iNOS marker expression was performed using rabbit polyclonal antibodies to iNOS. Results. Healthy skin cells showed almost no expressive staining during immunohistochemical determination of iNOS in the cells of the epidermis and dermis. When conducting similar studies of skin fragments of psoriasis patients a large number of positively stained cells in the epidermis, namely the basal, spinous and granular layers, were observed. Expression of iNOS in the investigated preparations looked as intracytoplasmic light and dark brown granules, which provided a homogeneous staining of cells of varying intensity. Cells of dermis in the papillary and reticular layer showed intense dark brown color of the majority of immune cells and fibroblasts. It was revealed that in the areas of skin lesions in patients with psoriasis and hypertension more cells and more intense immunohistochemical staining of the epidermis and dermis in the form of numerous moderate and dark brown intracytoplasmic inclusions were observed. Conclusions. When comparing the level of іNOS expression by U-Mann-Whitney test, a significant difference between the expression of iNOS in the epidermis in isolated psoriatic lesions and psoriasis in combination with hypertension (p <0.05) with significantly higher levels of expression in patients with comorbid disorders was established. In the dermis of the skin in patients with isolated psoriasis significantly lower iNOS expression was found in comparison with the psoriasis and hypertension patients skin (p <0.05).